Bantuan Dana Hibah Anggaran Pendapatan dan Belanja Daerah (APBD) dan Pengaruhnya Terhadap Kinerja Manajemen BAZNAS di Provinsi Sumatera Barat - Rini ELvira; Yaswirman Yaswirman; Nursyirwan Effendi; Dodi Devianto (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
This study aims to determine the causal-comparative relationship between the variable of APBD grant funding assistance and BAZNAS management performance. This study involved all BAZNAS in West Sumatra Province selected by total sampling with data sourced from PuskasBAZNAS publication. Simple linear regression analysis tested the comparative causal relationship between the two variables. The research show that the variable of APBDfunding does not affect to the management performance of BAZNAS in West Sumatra Province, but it is influenced by other factors, such as leadership, employees and organisational culture, availability of financial resources, governance, policies and strategies, technology utilisation, muzakki trust in BAZNAS, transparency and accountability, and local cultural values. The implication of this research is as a basis for future local government policy considerations in allocating APBD grant funding assistance, and for BAZNAS efforts to improve the efficiency and effectiveness of BAZNAS in zakat management.